The Analyses of Forest Fire Vulnerability at Taman Hutan Raya (Tahura) Nipa-Nipa Kendari City - Sahindomi Bana; Wa Ode Nur Hasanah; Laode Sabaruddin; Hasbullah Syaf; Lies Indriyani; Junartin Teke; La Gandri (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2022)
Forest fires are one of the environmental problems that recur almost every year in Indonesia. This problem if not handled properly will certainly cause various negative impacts such as the emergence of haze that can interfere with public health and reduced forest cover, in forest areas. Taman Hutan Raya Nipa-Nipa (Tahura) as one of the Natural Preservation areas of Southeast Sulawesi Province is also inseparable from the problem of forest fires. The aims of the study were to analyze the level of forest fire vulnerability in the Tahura Nipa-Nipa area, especially in Watu-Watu Village, West Kendari Subdistrict, and the variables that most affect the level of forest fire vulnerability. Data analysis based on the weighting of each element is then carried out the determination of the vulnerability class using equations: forest fire vulnerability = 30 % x (land cover) + (20 % x height of place) + (20 % x Rainfall) + (10 % x distance from road) + (10 % x distance from river) + (10 % x distance from settlement). Mapping the class of forest fire vulnerability areas using geoprocessing with input data on land cover, place height, rainfall, and distance from roads, rivers, and settlements. Then an analysis is carried out and will be selected data according to the score of the level of forest fire vulnerability, namely very low/not a vulnerability with a score of 5, low with a score of 4, medium with a score of 3, high with a score of 2, very high /very vulnerability with a score of 1. The results showed that the level of forest fire vulnerability in Tahura Nipa-Nipa has 3 levels, namely the level of high forest fire vulnerability with an area of 68.51 ha, the level of moderate forest fire vulnerability with an area of 62.29 ha, and the level of low fire vulnerability with an area of 143.35 ha. The variables that most affect the level of forest fire vulnerability at the research site are land cover and community accessibility distance in the form of distance from the road and distance from the settlement. Keywords: fire vulnerability, forest fire, Tahura Nipa-Nipa, Kendari